Advances in Behavioral Economics 2011
DOI: 10.2307/j.ctvcm4j8j.14
|View full text |Cite
|
Sign up to set email alerts
|

A Theory of Fairness, Competition, and Cooperation

Abstract: There is strong evidence that people exploit their bargaining power in competitive markets but not in bilateral bargaining situations. There is also strong evidence that people exploit free-riding opportunities in voluntary cooperation games. Yet, when they are given the opportunity to punish free riders, stable cooperation is maintained, although punishment is costly for those who punish. This paper asks whether there is a simple common principle that can explain this puzzling evidence. We show that if some p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

83
2,279
12
54

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,375 publications
(2,431 citation statements)
references
References 31 publications
83
2,279
12
54
Order By: Relevance
“…In a regression analysis they find the influence of outside options on bargaining results to be weaker than expected and the average share of the pie of the advantaged group to be smaller than the expected 0.6. They explain these results by a variant of the Fehr and Schmidt (1999) inequity aversion utility function…”
Section: Unstructured Bargaining (Anbarci and Feltovich 2013)mentioning
confidence: 89%
See 2 more Smart Citations
“…In a regression analysis they find the influence of outside options on bargaining results to be weaker than expected and the average share of the pie of the advantaged group to be smaller than the expected 0.6. They explain these results by a variant of the Fehr and Schmidt (1999) inequity aversion utility function…”
Section: Unstructured Bargaining (Anbarci and Feltovich 2013)mentioning
confidence: 89%
“…The assumption that incomplete matches are unstable requires values s j to be larger than À1. Fehr and Schmidt (1999) inequity aversion is specified in Appendix B. The altruistic core is depicted in Figure 1, where the effect of decreasing r W 1 is illustrated.…”
Section: The Core With Egoistic Preferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Workers who are inequity-averse have utility functions that increase in their own income, but decrease in the level of income inequality, as in Fehr and Schmidt (1999). If inequity aversion is an important concern, then we should expect a leaning towards team pay (compared to the principal-agent model).…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years, some researchers have found that the majority of the decision-makers has equity preference characteristics, they care not only their monetary payoffs but also fair treatment in the real life (Kahneman 1986 [13] ; Fehr 1999 [14] ; Frazier 1983 [15] ).…”
Section: Introductionmentioning
confidence: 99%